J Appl Physiol, Al-Shammari et. al. supplementary material - Gaffney, E; Al-Shammari, A; Egginton, S; Kissane, R; Holbek, S (University of Oxford, 2019)
This data provides executables to accompany the J Appl Physiol paper authored by AA. Al-Shammari, RWP Kissane, S Holbek, AL Mackey, TR Andersen, EA Gaffney, MK Kjaer and S Egginton, entitled "Integrated method for quantitative morphometry and oxygen transport modeling in striated muscle".